Solve and check the linear equation.
(-4x - 2) + 7 = -3(x + 3)

Question

Asked 8/26/2013 6:26:46 PM

Updated 6/27/2014 1:49:36 AM

6 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by jeifunk [6/27/2014 1:46:52 AM]

Micharnaezz|Points 120|

csnyder83|Points 1610|

andrewpallarca|Points 24883|

reynaldo009|Points 292|

clarebelle79|Points 180|

SOLUTION:

let x= answer/ simplified expression

x = -10(8r + 9) + 9(6r + 6)

x = -80r - 90+ 54r + 54

x = -80r + 54r - 90+ 54

x = -26r - 36

clarebelle79|Points 180|

Question

Asked 8/26/2013 6:26:46 PM

Updated 6/27/2014 1:49:36 AM

6 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by jeifunk [6/27/2014 1:46:52 AM]

Rating

3

-5(2x - 6) - 4x + 5

=(-5)(2x-6)+(-4x)+5

=(-14x)+35

=-14x+35

=(-5)(2x-6)+(-4x)+5

=(-14x)+35

=-14x+35

Added 6/27/2014 1:46:51 AM

This answer has been confirmed as correct and helpful.

3

The algebraic expression without parentheses : -(-2 + 7y) = -7y+2

Added 6/27/2014 1:48:12 AM

This answer has been confirmed as correct and helpful.

3

The algebraic expression without parentheses -(4x - 9) = -4x+9

Added 6/27/2014 1:48:46 AM

This answer has been confirmed as correct and helpful.

3

The algebraic expression without parentheses -(4x - 5) = -4x+5

Added 6/27/2014 1:49:36 AM

This answer has been confirmed as correct and helpful.

3x - 4 x = -4 **Weegy:** (3x^-4)^2 = 3x^-8 **User:** 6x + 2 x = 2 **Weegy:** x^2+6x+9 can be factorized as (x+3)^2. Source: **User:** 6x + 2 x = 2 **Weegy:** x^2+6x+9 can be factorized as (x+3)^2. Source: **User:** Evaluate the algebraic expression for the given value or values of the variable(s).
6x + 2 x = 2 **Weegy:** 6x + 2. 6(2) + 2, 12 + 2 = 4 (More)

Question

Expert Answered

Updated 8/21/2014 2:01:16 PM

2 Answers/Comments

If x=-4, 3x - 4=-16.

3x - 4

=3x(-4)-4

=-12-4

=-16.

3x - 4

=3x(-4)-4

=-12-4

=-16.

Added 8/21/2014 7:12:12 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/21/2014 2:01:19 PM], Rated good by andrewpallarca

Evaluate the algebraic expression for the given value or values of the variable(s).If x = 2 ,6x + 2 =14.

6x + 2

=6x2+2

=12+2

=14.

6x + 2

=6x2+2

=12+2

=14.

Added 8/21/2014 7:13:04 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/21/2014 2:01:39 PM], Rated good by andrewpallarca

3x - 4;x = -4 **Weegy:** 3x - 4; x=-4:
3(-4) - 4
= -12 - 4
= -16
(More)

Question

Expert Answered

Updated 8/21/2014 2:05:20 PM

0 Answers/Comments

Write the algebraic expression without parentheses.
-(-2 + 3y)

Question

Not Answered

Updated 76 days ago|4/30/2018 3:06:09 AM

1 Answer/Comment

-(-2 + 3y) = 2 - 3y

Added 76 days ago|4/30/2018 3:06:09 AM

This answer has been confirmed as correct and helpful.

Write the algebraic expression without parentheses.
-(4x - 5) **Weegy:** Result is (-4 x+7 y+4) (4 x+7 y-4) **User:** Write the algebraic expression without parentheses.
-(-2 + 3y) (More)

Question

Not Answered

Updated 238 days ago|11/18/2017 8:57:32 PM

2 Answers/Comments

27,075,865

questions answered

There are no comments.